Incidence and Time Trends of Pregnancy-Related Stroke Between 2010 and 2018: The Nationwide CONCEPTION Study. (11th October 2022) - Martin, Alice; Lailler, Grégory; Béjot, Yannick; Gabet, Amélie; Grave, Clémence; Regnault, Nolwenn; Chatignoux, Edouard; Moutengou, Elodie; Deneux-Tharaux, Catherine; Kretz, Sandrine; Mounier-Vehier, Claire; Tsatsaris, Vassilis; et al.
Abstract : Background and Objectives: Despite the potentially devastating effects of pregnancy-related stroke, few studies have examined its incidence by type of stroke. We aimed to study the nationwide incidence rates and recent temporal trends for all types of pregnancy-related stroke and to compare these incidences with stroke incidence in nonpregnant women. Methods: We conducted a study of 6, 297, 698 women aged 15–49 years who gave birth in France between 2010 and 2018 with no history of stroke before pregnancy by collecting data from the French National Health Insurance Information System database. Poisson regression was used to estimate the incidence by types of strokes for the different pregnancy periods and the incidence rate ratio of stroke in pregnant vs nonpregnant French women. Results: Among the 6, 297, 698 women, 1, 261 (24.0 per 100, 000 person-years) experienced a first ever stroke during, antepartum peripartum, or the first 6 weeks of postpartum. Of the pregnancy-related strokes, 42.9% were ischemic (IS), 41.9% were hemorrhagic (with similar proportion of intracerebral and subarachnoid hemorrhage), and 17.4% were cerebral venous thrombosis (CVT). Compared with nonpregnant women, incidence rates of stroke were similar during pregnancy for IS (adjusted incidence risk ratio [IRR] 0.9 [0.8–1.1]), slightly higher for all hemorrhagic strokes (IRR 1.4 [1.2–1.8]), and considerably increased for CVT (IRR 8.1 [6.5–10.1]). Pregnancy-related stroke incidence rose between 2010 and 2018 for IS and HS but was stable for CVT. Discussion: The risk of pregnancy-related CVT was more than 8-fold higher than that observed in nonpregnant women. The incidence of pregnancy-related IS and HS is increasing over time, and efforts should be made for prevention considering treatable cardiovascular risk factors and hypertensive disorders in pregnant women.